Accompaniment in making learning media to increase interest in learning at SDN Balongmojo Mojokerto - Ardianik Ardianik; Dheny Jatmiko; Wahyu Widayati; Mamang Efendy (University of Merdeka Malang, 2023)
School is a place for students to study. Often we meet in-class there are students who are less enthusiastic in studying and are less responsive to what is conveyed by the teacher. Students sometimes feel bored with lecture-based learning models, so educators need to conduct self-evaluations and improve the quality of learning in class. In this case, improving the quality of learning in the classroom can be done in various ways and teachers have a very important role in increasing students' interest in learning so that students feel comfortable and the knowledge they gain will be easy for them to accept. This study aims to analyze the use of instructional media in increasing students' interest in learning. The purpose of this service activity is to provide knowledge to SDN Balongmojo Mojokerto teachers about the use of plastic and paper waste to make innovative media. The target of this service is to provide information and assistance to teachers at SDN Balongmojo Mojokerto regarding the use of plastic waste and cardboard for making innovative learning media. The method used in this service is interactive training and mentoring. As a result of this community service activity, teachers at SDN Balongmojo Mojokerto are able to design, create, and practice making innovative media using plastic waste and cardboard